The effect of targeted subsidies on healthcare costs in rural areas - Zand, Azita; Arfaee , Masomeh; Ahmadi , Serveh (Social Determinants of Health, 2022)
Background: This study aimed to investigate the effect of targeted subsidies on health costs in the Khur and Biabank districts. Methods: This was descriptive-analytical research. The statistical population included 1326 heads of households in Khor and Biabank cities. Using the Krejcie and Morgan table, the statistical sample size was 300 people, who were selected by a random sampling method. The tool was a questionnaire. Experts confirmed its validity and its reliability were confirmed using a preliminary test and Cronbach’s alpha coefficient. Structural equation modeling was used in Lisrel and SPSS software. Results: Targeted subsidies with a factor load of 0.99 on the price of household appliances, with a factor load of 0.97 on the cost structure of education and cultural services, with a factor load of 0.96 on the cost structure of tourism, has a factor loading of 0.90 on the structure of transportation costs ,has a factor loading of 0.89 on the structure of housing and fuel costs, has a factor loading of 0.89 on the cost of agricultural products, has a factor load of 0.70 on the cost structure of food and tobacco, has a factor load of 0.69 on the cost structure of health and treatment. Conclusion: Due to the importance of the targeted subsidies effect on costs, the attention of policymakers in macro-planning is necessary.